Sectoral effects of a Green Tax Reform in Portugal. (April 2019) - Rodríguez, Miguel; Robaina, Margarita; Teotónio, Carla
Abstract: Economic downturn coupled with serious and persisting environmental problems require a new regulation system to tackle these problems. The Portuguese government created the Commission for the Green Tax Reform in 2014, following the guidelines of the European Union in the sense that fiscal policy should contribute to public budget consolidation and sustainable growth. The Commission was commissioned to propose a simplification of taxation in order to promote economic competitiveness, environmental sustainability and the efficient use of resources. The aim of this paper is to present the results from one of the teams that have contributed to the Commission for the Green Tax Reform. We have followed the European Commission guidelines in order to simulate a Green Tax Reform with a static general equilibrium model and aligned to the political context. We found that (i) it is possible to enjoy a positive double dividend, (ii) to achieve improvements in the energy-trade balance and energy independence and (iii) to reduce the energy intensity of the Portuguese economy. Highlights: This paper simulates a GTR according to the European Commission proposal launched in April 2011. The GTR may produce a positive double dividend. It achieves an improvement in the energy trade balance and energy independence. It contributes to reduce the energy intensity of the Portuguese economy. It may represent a fiscal devaluation policy tool in order to generate economic stimulus.